2013
DOI: 10.1186/1479-5868-10-92
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of psychological, social and behavioral barriers to appropriate food portion size control

Abstract: BackgroundGiven the worldwide prevalence of overweight and obesity, there is a clear need for meaningful practical healthy eating advice - not only in relation to food choice, but also on appropriate food portion sizes. As the majority of portion size research to date has been overwhelmingly quantitative in design, there is a clear need to qualitatively explore consumers’ views in order to fully understand how food portion size decisions are made. Using qualitative methodology this present study aimed to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…We have indeed demonstrated that perceptions about the healthiness of food can have a significant impact on food intake (i.e., "if it's healthy, I can eat more") [21]. Such perceptions have also been identified in a qualitative study in which participants talk about "guiltless eating" [22]. They mentioned that beliefs about healthy eating could influence portion control, with "healthy" foods being excluded from food intake monitoring [22].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We have indeed demonstrated that perceptions about the healthiness of food can have a significant impact on food intake (i.e., "if it's healthy, I can eat more") [21]. Such perceptions have also been identified in a qualitative study in which participants talk about "guiltless eating" [22]. They mentioned that beliefs about healthy eating could influence portion control, with "healthy" foods being excluded from food intake monitoring [22].…”
Section: Introductionsupporting
confidence: 54%
“…Such perceptions have also been identified in a qualitative study in which participants talk about "guiltless eating" [22]. They mentioned that beliefs about healthy eating could influence portion control, with "healthy" foods being excluded from food intake monitoring [22]. Overall, these findings suggest potential negative and unintended consequences of perceived healthiness of food on food choice and intake.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite the fact that portion size guidance tools/information are available via industry, healthcare professional and nongovernmental organisations, we found that the measurementstrategy scale carried the lowest score. Previous research has highlighted that the use of practices within this strategy may be hindered by the lack of clarity and irrelevance of portion size advice (Faulkner et al, 2012;Spence et al, 2013), while another study has highlighted the difficulties which consumers encounter when using portion size estimation aids. The second scale, eating-strategy, captures consumer efforts to serve less food and increase, induce or realise satiety (e.g.…”
Section: Tablementioning
confidence: 97%
“…Some regularly consumed larger portion sizes in order to impress, ingratiate themselves, or be a "good guest." 23,24 Importantly, providers that understand the context in which patient's ideals are set and how sociocultural ideals influence the type of behavioral self-regulation that develops can address these emotional barriers as part of the long-term goals of lifestyle modification for health maintenance. 25 The study by Segaret al 25 suggests that behavioral interventions might better facilitate increased physical activity among midlife women if providers address and acknowledge the internalization of cultural norms and pressures.…”
Section: Barriers In Societymentioning
confidence: 99%